Tools to Understand Social Issues in Energy Tariff and Subsidy Reforms in Europe and Central Asia - World Bank (Washington, DC, 2015)
This toolkit aims to help World Bank task teams working on energy subsidy and tariff reforms to develop qualitative analysis tools. The tools that are described in this document can help task teams to better understand and address social and political challenges related to these reforms, including impacts of reforms and political economy constraints. This toolkit shares lessons and research tools developed during analyses of energy tariff and subsidy reforms in ECA. In FY13-FY14 alone, the World Bank has been involved in providing guidance to over fourteen countries in the Europe and Central Asia (ECA) region on these reforms. World Bank assistance to ECA countries ranges from advice on the design of energy sector policies to understanding and mitigating poverty and social impacts. This toolkit presents a practical guide to applying the two sets of tools described above. Chapter two presents a brief overview of the types of social and political challenges in energy tariff reforms that motivate the use of qualitative and stakeholder or political economy assessments. Chapter three provides a step-by-step guide to conducting qualitative assessments and stakeholder analyses of energy tariff reforms based on the ECA experience. Annex one contains Terms of Reference (TORs) for all analytical tools described in the Toolkit. Annex two provides a reference table to case studies of PEAs of energy subsidy and tariff reforms conducted by the World Bank.